Unsettled Urban Space (Taylor & Francis, 2022)
While urban life can be characterized by endeavors to settle stable and safe environments, for many people, urban space is rarely stable or safe; it is uncertain, troubled, imbued with challenges and perpetually under pressure. As the concept of unsettled appears to define the contemporary urban experience, this multidisciplinary book investigates the conflicts and possibilities of settling and unsettling through open and speculative analysis.